The contributing external load factors to internal load during small-sided games in professional rugby union players - Zanin, Marco; Azzalini, Adelchi; Ranaweera, Jayamini; Weaving, Dan; Darrall-Jones, Joshua; Roe, Gregory (Frontiers in Sports and Active Living, 2023)
Introduction This study aimed to investigate which external load variables were associated with internal load during three small-sided games (SSG) in professional rugby union players. Methods Forty professional rugby union players (22 forwards, 18 backs) competing in the English Gallagher Premiership were recruited. Three different SSGs were designed: one for backs, one for forwards, and one for both backs and forwards. General linear mixed-effects models were implemented with internal load as dependent variable quantified using Stagno's training impulse, and external load as independent variables quantified using total distance, high-speed (>61% top speed) running distance, average acceleration-deceleration, PlayerLoad™, PlayerLoad™ slow (<2 m·s−1), number of get-ups, number of first-man-to-ruck. Results Internal load was associated with different external load variables dependent on SSG design. When backs and forwards were included in the same SSG, internal load differed between positional groups (MLE = −121.94, SE = 29.03, t = −4.20). Discussion Based on the SSGs investigated, practitioners should manipulate different constraints to elicit a certain internal load in their players based on the specific SSG design. Furthermore, the potential effect of playing position on internal load should be taken into account in the process of SSG design when both backs and forwards are included.